The Post Industrial City – Street Art and the “New” Cultural Agents in Barreiro, Portugal - Carmo, André (2020)
The municipality of Barreiro, near Lisbon, was an important industrial centre throughout the 20th century. Its development is inextricably linked to the implementation of a significant industrial chemical complex (CUF) and to the development of an extended railway infrastructure in the territory. During this period this territory experienced an intense development of a working class culture very linked to the anti-fascist resistance movements. In parallel, a strong associative civic movement grew and materialized in an important number of very dynamic local associations and collectivities. As the industrial activity began to decline in the 1970s the territory faced loss of population as well as abandonment and deterioration of industrial and housing infrastructures. One of the trends observed in the renovation of these territories has been the replacement of industrial activity by new services linked to arts and culture. These have become privileged instruments in processes of urban transformation. The ‘creative city’ and all that it encloses as the normative/analytical reference framework has become a structural component in local development strategies and policies. Street art may be considered one of the most visible sides of these transformation processes taking place in post industrial cities. With this frame of reference, we propose a critical analysis of the city of Barreiro, where both the resurgence of the associative movement and artistic interventions have been observed as the city seeks to recover from industrial decline and loss of population. In particular we look at: key cultural/artistic actors, dynamics and spaces, and street art manifestations.